A Simple Route to Synthesize Cu@Ag Core–Shell Bimetallic Nanoparticles and Their Surface-Enhanced Raman Scattering Properties. Issue 10 (October 2016) - Jin, Xia; Mao, Aiqin; Ding, Mengling; Ding, Peipei; Zhang, Tianchi; Gu, Xiaolong; Xiao, Wei; Yuan, Jin
Water-dispersed Cu@Ag core–shell nanoparticles (NPs) with 15 nm-diameter Cu core and 5 nm-thick Ag shell can be synthesized by a facile one-step chemical reduction at room temperature without any protective atmosphere. To obtain a homogeneous Ag coating on Cu, the influence of [Cu/Ag] molar ratio was investigated. Transmission electron microscopy (TEM) and X-ray diffraction (XRD) confirmed that Ag formed a dense coating on the surface of Cu, and that phase-pure spherical Cu@Ag core–shell bimetallic NPs were prepared when the [Cu/Ag] molar ratio was between 1/0.5 and 1/0.75. The time dependence of ultraviolet-visible (UV-Vis) spectra and XRD patterns of six-month stored Cu@Ag NPs showed that the as-prepared Cu@Ag NPs have a long-term antioxidant activity. Also, the surface-enhanced Raman scattering (SERS) signals had a high stability and reproducibility for the substrates. Hence, the as-prepared Cu@Ag nanostructures can be used as an efficient substrate for SERS signals.